Targeting intestinal microecology: potential intervention strategies of traditional Chinese medicine for managing hypertension - Yang, Zhihua; Lin, Shanshan; Liu, Yangxi; Song, Zhihui; Ge, Zhao; Fan, Yujian; Chen, Lu; Bi, Yingfei; Zhao, Zhiqiang; Wang, Xianliang; Wang, Yi; Mao, Jingyuan (Frontiers in Pharmacology, 2023)
Hypertension is the most significant risk factor in the global disease burden and has become one of the major public health problems in the world. At present, the pathogenesis of hypertension has still not been completely elucidated. In recent years, more and more evidence shows that intestinal microecology is closely related to the occurrence and development of hypertension, which provides a new way for the prevention and treatment of hypertension. Traditional Chinese medicine (TCM) has unique advantages in the treatment of hypertension. Taking intestinal microecology as the target, interpreting the scientific connotation of TCM in the prevention and treatment of hypertension may renew the treatment concept of hypertension again, so as to improve the therapeutic effect of hypertension. In this paper, the clinical evidence for TCM treatment of hypertension was firstly summarized. Next, the relationship between TCM and intestinal microecology was analyzed, as well as the correlation between intestinal microecology and hypertension. Finally, the methods by which TCM regulates intestinal microecology to prevent and treat hypertension were presented. In order to provide new research ideas for TCM prevention and treatment of hypertension and drug research.